Modification of REE distribution of ordinary chondrites from Atacama (Chile) and Lut (Iran) hot deserts: Insights into the chemical weathering of meteorites. (2nd June 2017) - Pourkhorsandi, Hamed; D'Orazio, Massimo; Rochette, Pierre; Valenzuela, Millarca; Gattacceca, Jérôme; Mirnejad, Hassan; Sutter, Brad; Hutzler, Aurore; Aboulahris, Maria
Abstract: The behavior of rare earth elements (REEs) during hot desert weathering of meteorites is investigated. Ordinary chondrites (OCs) from Atacama (Chile) and Lut (Iran) deserts show different variations in REE composition during this process. Inductively coupled plasma–mass spectrometry (ICP‐MS) data reveal that hot desert OCs tend to show elevated light REE concentrations, relative to OC falls. Chondrites from Atacama are by far the most enriched in REEs and this enrichment is not necessarily related to their degree of weathering. Positive Ce anomaly of fresh chondrites from Atacama and the successive formation of a negative Ce anomaly with the addition of trivalent REEs are similar to the process reported from Antarctic eucrites. In addition to REEs, Sr and Ba also show different concentrations when comparing OCs from different hot deserts. The stability of Atacama surfaces and the associated old terrestrial ages of meteorites from this region give the samples the necessary time to interact with the terrestrial environment and to be chemically modified. Higher REE contents and LREE‐enriched composition are evidence of contamination by terrestrial soil. Despite their low degrees of weathering, special care must be taken into account while working on the REE composition of Atacama meteorites for cosmochemistry applications. In contrast, chondrites from the Lut desert show lower degrees of REE modification, despite significant weathering signed by Sr content. This is explained by the relatively rapid weathering rate of the meteorites occurring in the Lut desert, which hampers the penetration of terrestrial material by forming voluminous Fe oxide/oxyhydroxides shortly after the meteorite fall.